2018
DOI: 10.1007/s00122-018-3099-1
|View full text |Cite
|
Sign up to set email alerts
|

STAYGREEN (CsSGR) is a candidate for the anthracnose (Colletotrichum orbiculare) resistance locus cla in Gy14 cucumber

Abstract: Map-based cloning identified a candidate gene for resistance to the anthracnose fungal pathogen Colletotrichum orbiculare in cucumber, which reveals a novel function for the highly conserved STAYGREEN family genes for host disease resistance in plants. Colletotrichum orbiculare is a hemibiotrophic fungal pathogen that causes anthracnose disease in cucumber and other cucurbit crops. No host resistance genes against the anthracnose pathogens have been cloned in crop plants. Here, we reported fine mapping and clo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(33 citation statements)
references
References 32 publications
0
32
1
Order By: Relevance
“…c). Similar trends were also observed for CsSGR expression in Gy14 and 9930 after inoculation with the ALS and AR pathogens (Pan et al ., ), supporting a direct link between CsSGR expression and host resistance against these pathogens.…”
Section: Resultsmentioning
confidence: 79%
See 4 more Smart Citations
“…c). Similar trends were also observed for CsSGR expression in Gy14 and 9930 after inoculation with the ALS and AR pathogens (Pan et al ., ), supporting a direct link between CsSGR expression and host resistance against these pathogens.…”
Section: Resultsmentioning
confidence: 79%
“…Our previous work (Pan et al ., ) has shown that CsSGR is a candidate gene for the AR resistance locus cla in PI 197087, suggesting that CsSGR in Gy14 is responsible for simultaneous resistances against DM, ALS and AR. To further confirm this, we conducted local association analysis in natural populations using sequencing data from the 93.7‐kb region and phenotypic data from a subset of lines (presented in Table S4).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations